Patient Preferences for Physician Attire in Ophthalmology Practices - De Lott, Lindsey B.; Panarelli, Joseph F.; Samimi, David; Petrilli, Christopher; Snyder, Ashley; Kuhn, Latoya; Saint, Sanjay; Chopra, Vineet; Whipple, Katherine M. (Journal of Academic Ophthalmology, 2019)
Importance Interest is growing in targeting physician attire to improve the patient experience. Few studies in ophthalmology have examined patient preferences for physician attire.Objective To understand patient preferences for physician attire in ophthalmology practices in the United States.Design Survey-based, cohort study.Setting Two private and two academic ophthalmology practices.Participants A convenience sample of patients receiving ophthalmic care between June 1, 2015 and October 31, 2016.Methods A questionnaire containing 22 questions and photographs of a male and female physician in seven forms of attire were presented to patients; 14 unique questionnaires were randomly distributed. Patient preference for physician attire was the primary outcome determined by summing ratings of how knowledgeable, trustworthy, caring, approachable, and comfortable the pictured physician made the respondent feel. One-way ANOVA assessed differences in mean composite scores. Comparisons between respondent demographics, practice type, and attire preferences were assessed by chi-square tests. Patient satisfaction was assessed by agreement with questions about importance of physician attire and whether this influences happiness with care.Results In total, 1,297 of 1,826 (71.0%) questionnaires were completed. Physician attire was rated as “important” by 62.9% of participants. A total of 43.6% of participants indicated that physician attire influenced how happy they were with their care. Overall, formal attire with white coat was preferred to casual, formal, and business attire (all comparisons, p < 0.05). No differences in composite scores between formal attire with white coat, scrubs alone, scrubs with white coat, or casual attire with white coat were observed. However, compared with formal attire with white coat, physicians wearing scrubs without white coat appeared less knowledgeable (mean [standard deviation]: 8.2 [1.8] vs. 7.4 [2.1]; p < 0.05) and trustworthy (8.3 [1.8] vs. 7.6 [2.1]; p < 0.05). Additionally, casual attire with white coat was rated as less knowledgeable compared with formal attire with white coat (7.4 [2.0] vs. 8.2 [1.8]; p < 0.05). Preferences for attire varied by clinical setting: patients preferred surgeons (45.2%) and physicians in emergency rooms (41.7%) in scrubs rather than formal attire with white coat.Conclusions Physician attire is important to patients receiving ophthalmic care. Policies aimed at physician attire in ophthalmology practices should be considered.
Keywords: physician attire; practice; patient experience